Transformative potential of the classical model of university - Kremen Vasyl (Borys Grinchenko Kyiv Metropolitan University, 2016)
The paper by Vasyl Kremen «Transformative Potential of the Classical Model of University» is devoted to the problem of the main challenges to university education in the ХХІ century. One of such challenges is innovative character of contemporary civilization and its high level of scientific and technological development. Research university is a kind of response to such challenge. Other important challenge is commercialization of university life in the context of globalization. Entrepreneurial and corporate universities could be regarded as a response to such challenge.